Analysis of Open-Ended Problem-Solving Ability in Mathematics in Terms of Cognitive Style - Nasifatul Mustafida; Muhammad Jamaluddin (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
Problem-solving ability is a fundamental skill. Problem-solving is an effort to find a way out of a difficulty to achieve a goal to be achieved. There are 4 stages in solving problems as follows: understanding the problem, planning a solution, implementing the plan, and checking back. This research method uses a qualitative approach. The goal is to explain the ability of open-ended problem-solving mathematics students in terms of cognitive style type Field Independent and Field Dependent. Selection of the subject of this study using cognitive style test instrument Group Embedded Figure Test (GEFT). The results of this study showed that the FI subject was able to answer correctly without any doubt and was able to answer the question independently while the FD subject was able to answer the question there was doubt but answered correctly and when answering the question asked the researcher.